Scientific and Technical Texts: Translation Aspects in Electrical and Computer Engineering - Irina Suima (Challenges and Issues of Modern Science)
Purpose. The purpose of the paper is to study the lexical and grammatical levels of technical documentation in the English and Ukrainian languages, as well as to analyze the means of expression of English technical documentation in the Ukrainian language in the field of electrical engineering and computer technology in order to achieve adequacy. Design / Method / Approach. Research methods: theoretical study and analysis of literary sources on the problem of research; methods of linguistic analysis: descriptive and comparative methods, methods of classification and systematization. Findings. It has been established that cultural differences have a significant impact on the perception of technical information, which determines the need to carefully consider the context and cultural features of both the source and target audiences. Theoretical Implications. As a result of the theoretical analysis, various approaches to the translation of culturally specific information in the scientific-technical text were considered. Translation of technical texts is one of the most responsible types of translation. Practical Implications. The practical value of this study is that the obtained results can be taken into account and used for: a) solving current issues of bilingual communication, contributing to ensuring the compliance of scientific and technical terminology with international standards; b) provision of practical recommendations on the translation of technical documentation; c) development of special educational courses that cover the theory and practice of scientific and technical translation, as well as the creation of manuals and dictionaries of technical terminology. Originality / Value. The scientific relevance of the study consists in highlighting the methods of translation of scientific and technical terminology, which is constantly updated through productive means of word creation. Research Limitations / Future Research. The study can serve as a basis for further studies in this field and improve the methods of translation of scientific and technical vocabulary. Paper Type. Practitioner paper.